Selection of green supplier by multi-moora combination method and two-stage clustering - Mahsa Niavand; Mohammad Amin Adibi; Adel Pourghader Chobar (مدیریت مهندسی و رایانش نرم)
Today, environmental management for companies with an emphasis on environmental protection has become one of the most important issues and global pressures require organizations to produce environmentally friendly products and services. This challenge has led to the creation of a new concept called green supply chain management in the field of business, which combines environmental thinking and supply chain. Also, the problems of green supplier selection methods have become a very important issue. a Hybrid supplier selection method, in the present study, is utilized to select the green supplier by combining the Tow-Step data clustering method and the MADM method which in this research is the MULTI MOORA method. A real-world case study is also presented at Etka Chain Stores which uses a questionnaire that measures the greenness of suppliers in 13 general criteria according to business context and criteria. The advantages of the proposed hybrid method are then discussed here to demonstrate its superiority.